Republic of San Marino : 2021 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for the Republic of San Marino. (IMF Staff Country Reports; Country Report ;, 2021)
San Marino entered the pandemic with substantial vulnerabilities and still struggling from the consequences of the Global Financial Crisis (GFC). However, the economy has shown significant resilience supported by a timely and targeted policy response. Fiscal support was substantially scaled up after external borrowing was secured, including through a debut Eurobond. The banking system was rationalized, partly capitalized, its liquidity substantially improved, and a strategy is being adopted to address exceptionally high nonperforming loans (NPLs). Some of these measures, while effective, have increased official public debt substantially.